P195 THE STRUCTURE OF A CONSULTATION HOUR FOR BENIGN DISEASES OF THE UPPER GASTROINTESTINAL TRACT AT A CENTRE OF EXCELLENCE FOR ESOPHAGEAL AND GASTRIC SURGERY. (23rd November 2019) - Knepper, L; Müller, D T; Fuchs, H; Fuchs, C; Brinkmann, S; Schröder, W; Bruns, C J; Leers, J M
Abstract: Aim: The aim of the study is to analyze the structure and the patient population of a consultation hour for benign diseases of the upper gastrointestinal tract at a centre of excellence for esophageal and gastric surgery. Background and Methods: The increasing specialization in visceral surgery leads to a higher number of special consultation hours, e.g. for benign diseases of the esophagus and stomach. In this study we examine both the reasons for an introduction at a specialized clinic and the therapy suggestions. The clinical and demographic data of all patients who visited an appointment for functional diseases of the upper gastrointestinal tract of the University Hospital Cologne during the entire year 2018 were collected prospectively for this study and evaluated at the end of the year. Results: In 2018, a total of 412 patients attended the benign OGI consultation hour (54% male). 107 patients (26%) attended more than once. 293 patients attended the consultation hour for the first time. The following diagnoses most frequently led to the presentation in the special consultation hour: GERD (n=262, 63%), achalasia (n=52, 13%), upside-down-stomach (n=24, 6%), dysphagia of unknown genesis (n=15, 4%), and other motility disorders of the esophagus (n=14, 3%). 190 patients received an EGD because they had not received an endoscopic examination in the last year. Functional diagnostics were performed in almost all new presentations: High- resolution-manometry (n=243), 24h-pH-metry (n=199). Even though the surgical department led the consultation hour, a conservative approach was recommended to 231 patients (56%). Surgery was recommended to 156 patients (38%) and an endoscopic approach was recommended in 25 cases (6%). Overall, 101 patients (43%) received an operation during the observation period. Most common indication for surgery was GERD (n=63, 62%). Of those 63 patients, 42 received a laparoscopic Nissen fundoplication. Conclusion: The demand for a specialized clinic for reflux treatment is significant and includes a high degree of diagnostics. A differentiation of the symptoms is decisive in order to select the right patients for surgical therapy. Only about every third patient is recommended for surgery.